ANALYSIS ON HEAT LOSS IN WATER HEATING TANK BASED ON TEMPERATURE SETTING VARIATION DURING NATURAL CIRCULATION FLOW USING FASSIP-02 TEST LOOP - Mulya Juarsa, S.Si., MESc.; Andrea Shevaladze Al Amin (HIMNI, 2022)
Based on the nuclear reactor accident in Fukushima due to an earthquake that caused a tsunami that turned off the electrical system for the cooling water pump. So that the reactor core melts due to the failure of the active cooling system, based on this incident, a passive cooling system that does not require external energy for emergency cooling is needed to prevent such an accident. Experimental research on the passive cooling system based on natural circulation flow to improve reactor thermal management performance during an accident has been done using the FASSIP-02 Test. One of the important components of the simulation of heat sources in nuclear power plants is the water heating tank (WHT). This study aimed to obtain the analysis results of heat absorption in water in WHT and the value of heat loss. The research method was carried out by calculating changes in the internal energy of water in WHT and heat loss for variations in water temperature settings from temperatures of 40 oC, 50 oC, and 60 oC in WHT at steady-state conditions for 5 hours experiment. The results showed that the entire surface of the tank resulted in heat losses of 10.85 kW, 9.2 kW, and 8.37 kW, which occurred at temperature settings of 40 oC, 50 oC, and 60 oC as a whole.